Alterations in jaw clenching force control in people with myogenic temporomandibular disorders. (December 2018) - Testa, M.; Geri, T.; Pitance, L.; Lentz, P.; Gizzi, L.; Erlenwein, J.; Petkze, F.; Falla, D.
Abstract: Isometric bite force control, via measures of force accuracy, force steadiness and force proprioception, was assessed in patients with myogenic temporomandibular disorders (TMDs) compared to healthy controls. Twelve people with myogenic TMDs and twelve age- and gender-matched asymptomatic controls performed maximal voluntary contractions (MVC) of unilateral jaw clenching followed by submaximal isometric contractions, with and without visual feedback of force, at 10, 30 50% and 70% MVC. Force performance was assessed with indices of accuracy (mean distance, MD) and precision (standard deviation, SD) and reported as a percentage of the MVC. A mixed-effect model was used to evaluate differences in MVC, MD and SD. The MVC was lower in the TMD group when clenching either ipsilateral or contralateral to the side of greatest pain (p < 0.05). No difference in MD was observed between groups. The SD depended on the interaction between group and painful side (p = 0.04) with the TMD group displaying higher SD when executing the task with the most painful side when compared to the ipsilateral or contralateral sides of the control group. The reduced maximal bite force and force steadiness observed in people with myogenic pain may interfere with masticatory function and should be considered when planning therapeutic interventions for TMDs.